An Analysis Of Cigarette Company Stock Price Difference Before And After The Excise Rate Increase (A Study Of Cigarette Companies Listed On The Idx) - Fadhilah Dzikrulla Akbar; Prastiwi, Arum (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
Cigarette excise increases in Indonesia have occurred every year starting from 2012. This year the government has increased cigarette excise rates by 10%. Increasing cigarette excise rates, which are included in government policy every year, can be one of the reasons for changes in share prices, especially in cigarette companies. Information before investing is very important for investors before making a decision. This research aims to determine differences in share prices in cigarette companies listed on the Indonesia Stock Exchange in 2023. This research is a comparative type of research that uses secondary data with documentation collection techniques. The analysis technique used in this research is Wilcoxon Signed Ranks. The research results show that there is a difference in the share price of Cigarette Companies before the increase in excise prices and after the increase in excise prices. After the announcement of the increase in cigarette excise prices, shares of cigarette companies experienced a decline.